СУЧАСНА ПРАВОВА МОДЕЛЬ СУСПІЛЬНИХ ВІДНОСИН СФЕРИ ЕЛЕКТРОННИХ ДОВІРЧИХ ПОСЛУГ В УКРАЇНІ - Костенко Олексій Володимирович (International Journal of Innovative Technologies in Social Science, 2019)
Legal relationships in the field of electronic trust services and digital signatures are regulated by the norms of international and national legislation, which provide a broad range of legal rights and obligations of legal entities in general. However, there are many areas of legal relations that are actually carried out by actors, but they are not regulated or insufficiently regulated by law. Thus, today the procedures for cross-border recognition of digital signatures certificates and electronic trust services are not regulated. It is social relations that arise during these procedures and processes that are subject to legal regulation, first of all, in the legislation of Ukraine. Taking into account the aforementioned objective of this article, there is a scientific analysis of the social relations existing in Ukraine in the field of digital signatures and electronic trust services, the development of proposals for the creation of a modern model of legal regulation of the operation of this sphere in a cross-border mode. The development of legislation and the introduction of the proposed new model of public relations will enable the application of modern rules of law for the recognition of foreign digital signature certificates and electronic trust services in a cross-border mode.